Implementasi Model Project-Based Learning Dengan Dukungan Teknologi Digital Pada Pendidikan Agama Kristen - Situmeang , Ameria; Hutabarat, Johannes; Sidabutar, Triades (JURNAL IMPARTA, 2026)
This study examines the implementation of the Project-Based Learning (PjBL) model supported by digital technology in the context of Christian Religious Education (PAK). PjBL is seen as an innovative approach capable of addressing the needs of 21st-century learning, particularly in developing students' critical thinking, creativity, collaboration, and communication skills. Through the integration of digital technologies, such as social media, online learning platforms, and creative applications, students are encouraged to produce real-life projects relevant to Christian faith values ​​and everyday life. Implementation results indicate that this approach increases learning motivation, spiritual understanding, digital literacy, and the quality of student work. Despite several challenges, such as limited technological resources, teacher competency, and time constraints, school managerial support and teacher training can be effective solutions. Thus, digital technology-based PjBL has proven to be a relevant strategy for enriching PAK, making learning more contextual, participatory, and transformative.